Pemanfaatan Whatsapp Untuk Menyebarkan Informasi Dari Pertamina Ke Paguyuban Spbu Di Sukoharjo - Indrastata, Ilham Buyung; Yuliana, Margaretha Evi (CV. ITTC INDONESIA, 2023)
The faster the times, we are required to be more responsive to everything that has to do with today's technology. One example of influential technology today is WhatsApp. The WhatsApp application facility is one of the information sharing facilities that is used to disseminate information quickly and accurately. WhatsApp as a medium for exchanging information with the employees of the SPBU Association in Sukoharjo Regency is divided into two parts, namely: first, identifying activities, socializing projects, conducting open coordination and determining projects in terms of: project formulation, determining project objectives. Implementation must be considered in the technical aspects including: facilities and infrastructure.